Peritoneal Dialysis Related Infections: Exit Site Infection & Care A quick review - Mohsin Riaz, Muhammad (Pakistan Journal of Kidney Diseases, 2021)
Catheter related infection is a major risk factor for catheter loss. Exit site infection is a type of catheter related infection. Infectious complications are the most common cause of technique failure and switching of peritoneal dialysis patients to hemodialysis. Adhering to hand hygiene principles that have been advocated by WHO can reduce the infectious complications. Exit site care starts prior to the implantation of the peritoneal dialysis catheter and includes proper positioning, use of prophylactic antibiotics and patient education. The early identification of exit site infection is the key to proper treatment and prevention of peritoneal dialysis catheter loss. The empirical antibiotics therapy should be started immediately after taking the culture swabs. In conclusion, healthy exit site is key for successful peritoneal dialysis program. It can only be accomplished by regular surveillance of exit site and proper patient education.